Masyarakat Madani: Visi Etis Islam Tentang Civil Society - Wawan Mas'udi (Jurnal Ilmu Sosial dan Ilmu Politik, 1999)
Notion of civil society referring to different thing from time to time. Theoretically the term is used to refer to four different things: (1) as the facet within the formation of the state, (b) as a hegemonic power of the dominating class, (c) as autonomous societal associations capable of controlling the state, and (d) as ethical spirit of in governing the public. Islamic community attempt to enrich the discourse and frame the process of democratization by mobilizing ethical spirit outlined as egalitarianism, pluralism, tolerant and deliberation. This article attempts to trace its both the religious and historical bases for advocating the notion of 'Madanian society' (widely used in Indonesia as masyarakat niadani) instead of its original term 'civil society'.